Randomized clinical trial of mast cell inhibition in patients with a medium‐sized abdominal aortic aneurysm. Issue 8 (12th May 2015) - Sillesen, H.; Eldrup, N.; Hultgren, R.; Lindeman, J.; Bredahl, K.; Thompson, M.; Wanhainen, A.; Wingren, U.; Swedenborg, J.; the AORTA Trial Investigators; Wanhainen, A.; Hultgren, R.; et al.
<x xml:space="preserve">Abstract</x> Background Abdominal aortic aneurysm (AAA) is thought to develop as a result of inflammatory processes in the aortic wall. In particular, mast cells are believed to play a central role. The AORTA trial was undertaken to investigate whether the mast cell inhibitor, pemirolast, could retard the growth of medium‐sized AAAs. In preclinical and clinical trials, pemirolast has been shown to inhibit antigen‐induced allergic reactions. Methods Inclusion criteria for the trial were patients with an AAA of 39–49 mm in diameter on ultrasound imaging. Among exclusion criteria were previous aortic surgery, diabetes mellitus, and severe concomitant disease with a life expectancy of less than 2 years. Included patients were treated with 10, 25 or 40 mg pemirolast, or matching placebo for 52 weeks. The primary endpoint was change in aortic diameter as measured from leading edge adventitia at the anterior wall to leading edge adventitia at the posterior wall in systole. All ultrasound scans were read in a central imaging laboratory. Results Some 326 patients (mean age 70·8 years; 88·0 per cent men) were included in the trial. The overall mean growth rate was 2·42 mm during the 12‐month study. There was no statistically significant difference in growth between patients receiving placebo and those in the three dose groups of pemirolast. Similarly, there were no differences in adverse events. Conclusion Treatment with pemirolast did not retard the growth of medium‐sized AAAs. Registration number: NCT01354184 (https://www.clinicaltrials.gov).